descompuneti: x²-10x-11
Răspunsuri la întrebare
Răspuns de
8
x² - 10x - 11 =
x² -10x - 10 -1 =
(x² - 1 ) - 10 (x +1 ) =
(x + 1)(x -1) - 10 (x +1) =
(x + 1) ( x - 1 - 10) =
(x + 1) (x - 11)
x² -10x - 10 -1 =
(x² - 1 ) - 10 (x +1 ) =
(x + 1)(x -1) - 10 (x +1) =
(x + 1) ( x - 1 - 10) =
(x + 1) (x - 11)
HawkEyed:
corectez ))
Răspuns de
5
=x la 2+x-11x-11
=x(x+1)-11(x+1)
=(x-11)(x+1)
=x(x+1)-11(x+1)
=(x-11)(x+1)
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă